Evidence-Based Procedural Dermatology - Alam, Murad; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
In Evidence-Based Procedural Dermatology, Dr. Alam has compiled the subspecialty’s latest research findings in a reference for researchers and dermatologists. It covers the spectrum of procedural dermatology, including skin cancer surgery, laser techniques, fillers and neurotoxins, minimally invasive cosmetic surgery, and emerging procedures. Leading experts present and evaluate evidence in each subfield, providing a solid manual for the present, and a guide for research in the future. Features: ·         A numerical system to appraise research findings used throughout the book ·         Question and answer section to reinforce knowledge at the end of  most chapters ·         Serves as a tutorial for those interested in performing clinical research. ·         Holds practical value for dermatologists who are treating or counseling patients.
1.Mohs Surgery -- 2.Basal Cell Carcinoma -- 3.Cutaneous Squamous Cell Carcinoma -- 4.Melanoma Surgery -- 5.Merkel Cell Carcinoma -- 6.Photodynamic Therapy -- 7.Treatment of Precancers with Topical Agents -- 8.Reconstruction: Flaps, Grafts and Other Closures -- 9.Prevention and Treatment of Scars -- 10.Prevention and Treatment of Procedure-Associated Infection -- 11.Prevention and Treatment of Bleeding Complications in Dermatologic Surgery -- 12.Vascular Lasers and Lights -- 13.Pigment Lasers and Lights -- 14.Ablative Resurfacing: Laser, Chemical Peels, and Dermabrasion -- 15.Nonablative and Minimally Ablative Resurfacing -- 16.Non-Surgical Lifting and Tightening -- 17.Non-Laser Superficial Resurfacing Techniques: Superficial Chemical Peels and Microdermabrasion -- 18.Cosmeceuticals -- 19.Botulinum Toxin -- 20.Soft Tissue Augmentation -- 21.Liposuction -- 22.Hair Transplantation -- 23.Face Lifting -- 24.Blepharoplasty -- 25.Cellulite -- 26.Non-Invasive Body Contouring.
Keywords: Dermatology; Dermatology